Endoscopic biliary drainage outperforms conventional external drainage in pediatric choledochal cyst with severe cholangitis: a retrospective cohort study - Guo, Hongxi; Luo, Juan; Chen, Jingjing; Yang, Jun; Bian, Hongqiang; Yang, Hu; Duan, Xufei; Wang, Xin (Frontiers in Pediatrics, 2025)
BackgroundCholedochal cyst (CC) is a common biliary malformation in children and is often associated with severe cholangitis. While endoscopic biliary drainage (EBD) is well established in adults, its efficacy and safety in children remain unclear. This study aimed to compare the effectiveness and safety of EBD with conventional external drainage (CED) in children with CC complicated by severe cholangitis.MethodsClinical data from children with CC complicated by severe cholangitis who were treated at Wuhan Children's Hospital between January 1, 2013, and January 31, 2025, were retrospectively analyzed. Patients were divided into CED and EBD groups based on the drainage method. Various clinical outcomes were compared between the two groups, including operative time, intraoperative bleeding, postoperative hospitalization duration, pain scores, complication rates, time to radical surgery, conversion to open surgery, and laboratory indices.ResultsFifty-nine children (CED: n = 31; EBD: n = 28) were included (12 males and 47 females, with a mean age of 3.21 ± 2.17 years). Compared with CED, the EBD group demonstrated significantly better outcomes, including a shorter operative time (P < 0.001), less blood loss (P < 0.001), reduced length of stay (3.2 vs. 6.5 days, P < 0.001), lower pain scores (2.1 vs. 5.8, P < 0.001), fewer complications (3.57% vs. 25.81%, P = 0.044), shorter radical surgery interval (14 vs. 28 days, P = 0.002), and lower laparotomy conversion rate (3.57% vs. 29.03%, P = 0.024). Both groups demonstrated statistically significant differences in postoperative 24 h reductions of total bilirubin and transaminase levels (P < 0.05).ConclusionsIn children with CC complicated by severe cholangitis, EBD provides significant advantages over CED. It is less invasive, which leads to faster recovery times and lower complication rates, making it the preferred transitional treatment before definitive surgery.